PENDEKATAN FLEKSIBEL DAN ADAPTIF TERHADAP PENCIPTAAN BISNIS INDONESIA SAAT INI - Ingrid Panjaitan; Inge Gunawan (Mount Hope Management International Journal, 2025)
This study explores flexible and adaptive approaches to business creation in Indonesia, amidst rapidly changing economic dynamics due to digitalization, the pandemic, and regulatory changes. Using the theoretical framework of organizational agility and entrepreneurial orientation, the study analyzes how Indonesian entrepreneurs implement adaptive strategies to enhance business resilience and innovation. Using mixed methods, data was collected from 200 MSMEs across various sectors. Results show that flexible approaches are significantly correlated with improved business performance, with technology adaptation being a key factor. Implications for entrepreneurship policy and practice are discussed, emphasizing the importance of a dynamic supporting ecosystem.